Immune Thrombocytopenia in a Child with Neuroblastoma. (14th September 2017) - Ikizoglu, Hasan Tarkan; Ayan, Inci; Tokat, Fatma; Tecimer, Tulay; Topuzlu Tekant, Gonca
Abstract : Thrombocytopenia is a frequent finding in patients with solid tumors. It is usually caused by bone marrow infiltration or by myelosuppression due to anticancer therapy; however immune thrombocytopenia (ITP) associated with solid tumors is rare. Neuroblastoma is the most common extracranial solid tumor in children. Here we report the case of a two-year-nine-month-old patient with adrenal neuroblastoma who presented with ITP. Paraneoplastic ITP was considered in the differential diagnosis. Bone marrow infiltration and other causes of thrombocytopenia were excluded and the patient was treated with intravenous immunoglobulin and tumor resection. Platelet count increased rapidly after surgery and complete remission of ITP was achieved.